Bonding performance between distinct layers of cast-in-situ self-compacting concrete and ordinary concrete. (10th April 2023) - Yuan, Qiang; Chen, Ruonan; Zuo, Shenghao; Huang, Tingjie; Zhang, Kai; Mei, Da
Highlights: The influence of time intervals and curing ages on the bonding strength of the composite specimens was studied. The failure mode and microstructure of the composite specimens were analyzed. The bond strength prediction model was proposed and verified. Abstract: The issue of concrete vibration in the continuous beam 0# block is resolved by using a combination of self-compacting concrete (SCC) and ordinary concrete (OC). As a consequence of the multi-layer casting technique, SCC-OC structures consist of two layers and a bonding interlayer, so the bonding performance is crucial to guarantee the reliability of the structure. This paper studies the bonding performance between distinct layers of SCC and OC and attempts to establish the relationship between the two parameters (i.e., casting time interval and curing age) and the bonding strength (i.e., spitting strength and shearing strength). The results indicate that the casting time interval between SCC and OC has a stronger effect on the failure mode than that of curing age, and the shearing test can better characterize the weakly bonded interface than the splitting test. A shorter casting time interval and a longer curing age lead to higher bonding strength. Based on the bonding micro-mechanism and failure modes of SCC-OC interfaces, a mechanical model is proposed to predict the shear strength of the SCC-OC composite. The innovative approach of combining SCC and OC is promising to solve the problem of concrete vibration in the continuous beam 0# block at a low cost.